Increased risk of psoriasis in subjects with abdominal obesity: A nationwide population‐based study. Issue 8 (31st May 2019) - Han, Ju Hee; Lee, Ji Hyun; Han, Kyung Do; Kim, Ha‐Na; Bang, Chul Hwan; Park, Young Min; Lee, Jun Young; Kim, Tae Yoon
Abstract: Psoriasis is a chronic inflammatory skin disease known to be associated with a variety of systemic comorbidities, such as metabolic syndrome and obesity. Obesity represents a major comorbidity and has been suggested to be related to psoriasis. This nationwide population‐based prospective cohort study was performed to investigate the impacts of body mass index (BMI) and waist circumference (WC) on psoriasis. We used the health check‐up database and the study population consisted of subjects who had undergone health screening between January 2009 and December 2012. This study investigated patients newly diagnosed with psoriasis (International Classification of Disease, Tenth Revision, code L40) by dermatologists during the follow‐up period (5.32 years), based on claims data. The total population consisted of 22 633 536 subjects, among whom 399 461 had newly developed psoriasis. Subjects with BMI of more than 30 had a higher risk of psoriasis (hazards ratio [HR], 1.118; 95% confidence interval [CI], 1.100–1.137) compared with the BMI 18.5–23 group. WC showed a dose‐dependent association with psoriatic risk. Subjects with WC over 105 cm showed the highest risk of psoriasis (HR, 1.305; 95% CI, 1.261–1.349) compared with subjects with WC lower than 80/75 after adjusting for confounding factors, including BMI. The risk of psoriasis was highest in males with normal BMI and abdominal obesity (HR, 1.175; 95% CI, 1.150–1.200). Our study indicates that WC is a specific factor affecting psoriatic risk and highlights the association between abdominal obesity and psoriasis, thus increasing awareness of the role of abdominal obesity in the pathogenesis and comorbidities of psoriasis.